Governance of portfolios, programs, and projects : a practice guide - Project Management Institute (Pennsylvenia Project Management Institute, 2016)
This practice guide provides definitions for governance in an effort to distinguish the different levels of governance and to identify their common elements
Includes bibliographical references.
osc 08/01/2019, ijb, 29/01/2019
Loans
Keywords: Project management; Portfolio management